PHYSICAL THERAPY OF MIDDLE-AGED PEOPLE WITH GONARTHROSIS AT THE OUTPATIENT STAGE OF REHABILITATION (Physical Culture and Sport: Scientific Perspective, 2025)
Gonarthrosis is one of the most common forms of osteoarthritis, which is accompanied by a significant decrease in functional activity, chronic pain syndrome and deterioration of the quality of life of patients. The insufficient number of studies devoted to the optimization of physical therapy programs for middle-aged people with gonarthrosis at the outpatient stage determines the need to develop scientifically based approaches. Purpose of the study: to determine the effectiveness of physical therapy for middle-aged people with gonarthrosis at the outpatient stage of rehabilitation. Research methods. The work used theoretical research methods: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodological literature, empirical methods and methods of mathematical statistics. Results of the work. At the outpatient stage of rehabilitation, physical therapy plays an important role in restoring knee joint function, relieving pain, reducing inflammation and improving motor activity of patients. Specially selected exercise programs, including low-intensity loads, allow you to reduce pain and prevent complications such as muscle atrophy and joint mobility limitation. At the end of the study, the results on the Lower Extremity Functional Scale showed an improvement in functional status in both groups. In the main group (OG), the indicator increased from 50.26 to 71.25 points, which indicates a significant improvement in the functioning of the lower extremities after the developed therapy program (p0.05). Conclusions. Physical therapy should not be the only method of treating gonarthrosis. It should be part of a comprehensive approach, which also includes lifestyle changes, proper nutrition, weight control, and drug treatment if necessary. A comprehensive approach allows you to achieve better results in the treatment and restoration of joint functions.
Keywords: knee joint; physical therapy; functional state; range of motion